Translation and cultural adaptation of instruments to assess the predisposition of assistive technology use that constitutes the matching, person & technology model - Braccialli, Lígia Maria Presumido [UNESP]; Braccialli, Ana Carla [UNESP]; Audi, Mauro [UNESP]; Scherer, Marcia (FapUNIFESP (SciELO), 2019)
The Matching, Person & Technology (MPT) conceptual model proposes a user-centered, environment-oriented approach for prescription of Assistive Technology, by means of standardized instruments, in order to facilitate the process of correspondence between user and technology. The aim of the study was to translate and adapt culturally to the Portuguese of Brazil the Initial Worksheet for the Matching Person & Technology Process; History of Support and Healthcare Technology Device Predisposition Assessment-HCT PA that make up the MPT model. The study was attended by two sworn translators, three researchers whose native language was Portuguese and had fluency in English with an area of Assistive Technology, a translator whose native language was English and had fluency in Portuguese and the coordinator of the project, the author of the original instrument, five judges with experience in the area of Assistive Technology and Master’s or PhD in Education with an emphasis on Special Education and six health and education professionals with experience in dispensing Assistive Technology for people with disabilities. The research was divided into 5 stages: 1) translation of the instrument, 2) reconciled translation, 3) back translation, 4) equivalence of item analysis and adequacy of the instrument, and 5) pre-test. The results indicated a high index of agreement among the participants and a good cultural equivalence of the instruments. It is concluded that the Portuguese of Brazil versions of the instruments have a good acceptability and are suitable to be used for the prescription of technology for Brazilian users.
Tradução e adaptação cultural de instrumentos para avaliar a predisposição do uso de tecnologia assistiva que constitui o modelo matching, person & technology
Keywords: Access to technology; Assistive Technology; Scale of evaluation; Special Education